MOTIVATIONAL FACTORS FOR THE PRACTICE OF PHYSICAL EXERCISES IN WOMEN IN THE AGING PROCESS (Fiep Bulletin - online, 2019)
The aging process brings with it a series of modifications that affect the individual, such as the decrease of thefunctional capacity and quality of life in general. From the need to carry out interventions that improve the functional capacity andquality of life of individuals, several physical exercise programs were created. The present study aimed to verify the main reasonsfor adherence to the practice of physical exercise by analyzing the motivational determinants of aging women for participation inan exercise program, evidencing the variable age group. Participants were divided into two groups: up to 64 years (n=14) andgroup above 65 years (n=14). The Inventory of Motivation for the Regular Practice of Physical Activities (IMPRAF-54) was usedas an instrument for data collection. It was verified that the motivational factors health, pleasure and sociability were the mostevidenced dimensions by the age groups in relation to the influence in the adherence to the practice of physical exercise,especially the younger group that presented higher values in the health dimension. The results of the study show that inidentifying the motivational factors that most influence individuals to adhere to physical activity programs, it becomes possible tocreate new strategies for programs aimed at this audience, becoming more attractive.
Keywords: Physical Activity; Elderly; IMPRAF-54